Complex assessment of narrow-leaved lupine (Lupinus angustifolius L.) accessions from the VIR collection in Belarus - V. S. Anokhina; I. Yu. Ramanchuk; I. B. Sauk; G. P. Egorova; M. A. Vishnyakova (Труды по прикладной ботанике, генетике и селекции)
Fifty narrow-leaved lupine accessions of various origin from the VIR collection were studied in Minsk District, Republic of Belarus, and described by a set of morphobiological, biochemical and molecular-genetic characters. According to the results of field and laboratory studies, 10 promising accessions were selected. They are recommended for use in regional breeding programs and included in the working collection of the Belarusian State University.